Implementation of Good Manufacturing Practice and Marketing Digitalization at KWT Karya Tani in Purbalingga - Muhammad, Katon; Safitri, Telma Anis; Sari, Suci Wulan (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2026)
The empowerment of the Women Farmers’ Group (Kelompok Wanita Tani/KWT) Karya Tani in Purbalingga Kidul Village was carried out through the implementation of Good Manufacturing Practice (GMP) and marketing digitalization to enhance the production capacity of “Nata Baya” aloe vera candied products. This study employed a participatory action research approach, involving 12 KWT members as research subjects. The interventions consisted of four main activities: (1) training on the use of an aloe vera peeling machine, (2) socialization of quality control practices and food safety standards, (3) training on optimal working posture, and (4) the creation of marketplace accounts along with digital marketing training. The findings revealed a 50% increase in production efficiency, with production capacity rising from 10 kg to 20–22 kg per day. The implementation of GMP improved participants’ understanding of food safety by 25%. The marketing digitalization program successfully enhanced digital marketing skills, with 100% of members able to use Canva and 75% capable of creating promotional posts independently. Furthermore, the rebranding efforts through packaging design transformation received positive responses.